Sub-cultural differentiation of family ethos in terms of yalues related to child deyelopment - Dryll, Elżbieta (Studia Psychologica: Theoria et praxis, 2009)
The research refers to the cross-cultural paradigm in family studies. It was aimed to test an influence of two important cultural factors on the values connected with the child rearing process. The first factor is a nationality (the German minority or the Polish majority). The second factor is religiousness (affiliation to Jehova-sect or to Roman Catholics). Each of the compared groups live in the same society - in Poland. Two other demographic variables have been controlled: an educational level of parents and a family residence (a city or rural area). The values which direct the child rearing process within a family were diagnosed with a use of a technique based on toys advertisements. The issues indicate some important differences in that domain. For example: Polish Roman Catholics living in a rural area pay attention to an intellectual development of children, while Polish Roman Catholics of the city appreciate spiritual, artistic and physical development. Both minority groups take care of a social development but, what is interesting, members of the Jehova-sect neglect an importance of spiritual development. The conclusions of that study contribute to the understanding of the cultural impact in socialization within family surrounding.